2011
DOI: 10.4028/www.scientific.net/amm.148-149.1179
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Austenitic Steel TP347HFG Exposed to Supercritical Water with Different Dissolved Oxygen Concentration

Abstract: The oxidation of austenitic fine-grained steel TP347HFG exposed to supercritical water at 550 °C and 25 MPa with the dissolved oxygen concentration of 100 ppb, 300 ppb and 2000 ppb was investigated. The results indicated weight gain increased with the dissolved oxygen increasing. The herpes-shaped oxides were formed on the sample surface. The oxide layer was a typical dual-layered structure with a Fe-rich outer layer and a Fe-Cr-Ni-rich inner layer. The influences of the dissolved oxygen concentration and grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The EDS results suggested that high levels of niobium element accumulated in the corrosion pits. It seemed that the corrosion pits might be determined by inclusions of NbC [ 31 , 38 , 39 ]. In high-temperature water, pitting may be associated with Nb-rich precipitates (likely the γ '-phase) [ 4 , 40 ] and induced by local potential difference between the matrix and the inclusions [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…The EDS results suggested that high levels of niobium element accumulated in the corrosion pits. It seemed that the corrosion pits might be determined by inclusions of NbC [ 31 , 38 , 39 ]. In high-temperature water, pitting may be associated with Nb-rich precipitates (likely the γ '-phase) [ 4 , 40 ] and induced by local potential difference between the matrix and the inclusions [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Austenitic steel TP347HFG, a modified form of TP347H, having a fine grain structure, has been developed for use in the finishing stages of reheater and superheater boiler tubes . Several separately studies on oxidation and creep rupture properties of TP347HFG can be found in the literature .…”
Section: Introductionmentioning
confidence: 99%